Effective Strategies to Enhance Collaborative Skills of Healthcare Workers in Improving Patient Satisfaction: A Systematic Review - Sri Wahyuni; Iis Rahmawati; Rondhianto Rondhianto (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2026)
One of the most important factors in raising hospital patient happiness and care quality is effective collaboration among healthcare professionals. Implementing techniques to improve teamwork skills is still fraught with difficulties, though. A lack of policy backing, a lack of resources, and healthcare personnel' aversion to change are the key problems. Health workers' resistance to change, a lack of legislative support, and a lack of resources all make it difficult to maximize team collaboration, which is crucial for providing high-quality care and satisfactory patient outcomes. Therefore, in order to assess the efficacy of collaborative skills training programs and their influence on patient satisfaction, a systematic study is required. A thorough literature review based on major databases was conducted in this investigation. The Scopus, PubMed, Web of Science, and Google Scholar databases were searched for relevant literature with a publication span of 2019–2024. The Joanna Briggs Institute (JBI) and the Mixed Methods Appraisal Tool (MMAT) were used to assess the gathered papers. Eight pertinent articles were thoroughly examined out of the 885 total that were found. To find important trends in health workers' collaborative skills training tactics and their effects on patient satisfaction, a theme analysis technique was used to examine a few chosen research. Eight publications in all were gathered, and the results demonstrated that online learning and simulation-based training improved health workers' capacity for teamwork. Additionally, it has been demonstrated that clinical supervision and leadership enhance the coordination of multidisciplinary teams, and family-based approaches significantly affect patient satisfaction. This study recommends hospitals include these evidence-based training tactics into postoperative care protocols to enhance team efficacy and overall patient experience, notwithstanding implementation hurdles such time restrictions and managerial support. Enhancing interdisciplinary teamwork through structured collaborative training can improve patient outcomes and satisfaction while also enhancing the quality of treatment. This method encourages teamwork and collaborative decision-making while promoting integrated, holistic care in nursing. Improved care quality, enhanced team communication, and a patient-centered approach involving families are among the health implications. These tactics benefit patients and healthcare professionals alike, improving clinical results, patient safety, and general satisfaction.